FAO-ILRI training helps Africa livestock specialists address gender issues in their daily work - Distefano, F. (International Livestock Research Institute, 2012)
In November 2011, Francesca Distefano, Gender and Development consultant at the Food and Agriculture Organization joined a training workshop on integrating gender in livestock projects and programs for FAO country livestock officers and partners from East and Southern Africa. The workshop aimed to help participants understand the key issues of gender and livestock and to ensure that projects are designed to be gender sensitive and gender responsive. It provided them with a tool and checklist to help them address gender in a more comprehensive way.